PERUMUSAN FALSAFAH PEWAYANGAN DALAM NORMA HUKUM - Bambang Sadono (Faculty of Law, Universitas Diponegoro, 2012)
Abstract Puppet art, especially the content of his philosophy, is very rich in references to the life of nation and state building are ideal. Puppet raises many pearls of wisdom that is useful in many national and state life.Existence and expression of the philosophy of puppetry, more of the institutionalization of the values of personal and social. Personal and social norms, their enforcement depends on the personal moral awareness or community concerned. Actually be more effective if its institutionalization through legal norms, because the state has the obligation to guard it. But the institutionalization of these values into the philosophy and culture have not been conducted with the maximum norm. To facilitate, to rich culture including philosophy, could be a reference source of civic life, it takes an umbrella and national recognition in the form of legislation. It required a systematic effort to strive for indigenous culture and philosophy of Indonesia, is really the soul of and politics of national law. Keywords : Formulation, Puppet Philosophy, Legal Norms Abstraksi Kesenian wayang, khususnya kandungan filsafatnya, sangat kaya akan tuntunan kehidupan bangsa untuk membangun negara yang ideal. Di dalam kesenian Wayang banyak terkandung kebijaksanaan yang berguna dalam kehidupan berbangsa dan negara. Keberadaan dan ekspresi dari filosofi wayang, lebih dari pelembagaan nilai-nilai pribadi dan sosial. Penegakan norma tersebut tergantung pada kesadaran moral pribadi atau masyarakat yang bersangkutan. Sebenarnya lebih efektif jika melalui pelembagaan dalam norma hukum, karena negara memiliki kewajiban untuk menjaganya. Tapi pelembagaan nilai-nilai ini ke dalam filsafat dan budaya belum dilakukan dengan maksimal. Untuk memudahkannya, budaya yang kaya filsafat, bisa menjadi sumber referensi dari kehidupan masyarakat. Maka dibutuhkan payung hukum dan pengakuan Negara dalam bentuk undang-undang. Untuk itu diperlukan upaya sistematis dalam memperjuangkan budaya, adat dan filosofi Indonesia kedalam sistem politik dan hukum nasional Kata kunci : Perumusan, Falsafah Wayang, Norma Hukum